Synthesis and Biological Evaluation of New 2-Azetidinones with Sulfonamide Structures - Dragos Pieptu; Ramona Florina Moraru; Valentin Nastasa; Mihai Mares; Cornelia Vasile; Florentina Lupascu; Oana Maria Dragostin; Lenuta Profire (Molecules, 2013)
New series of N-(arylidene)hydrazinoacetyl sulfonamides 4a1–6, 4b1–6 and N-(4-aryl-3-chloro-2-oxoazetidin-1-yl)aminoacetyl sulfonamides 5a1–6, 5b1–6 were synthesized. The structures of the new derivatives was confirmed using spectral methods (FT-IR, 1H-NMR, 13C-NMR). The antibacterial activities of these compounds against Gram positive (Staphyloccoccus aureus ATCC 6583, Staphyloccoccus epidermidis ATCC 12228, Enterococcus faecalis ATCC 25912) and Gram negative (Klebsiella pneumoniae CIP 53153, Proteus vulgaris CIP 104989, Citrobacter freundii CIP 5732, Enterobacter cloacae CIP 103475, Escherichia coli ATCC 25922, Pseudomonas aeruginosa CIP 82118) bacterial strains were evaluated using the broth micro-dilution method. Compound 4a2 displayed the highest antibacterial activity, especially against Staphyloccoccus epidermidis, Enterococcus faecalis and Pseudomonas aeruginosa. The antioxidant potential of the synthesized compounds was also investigated according to ferric reducing power, total antioxidant activity and DPPH radical scavenging assays. All tested compounds showed excellent antioxidant activity in comparison with sulfadiazine and sulfisoxazole which were used as parent sulfonamides. Moreover, some of them showed an antioxidant activity comparable with that of ascorbic acid. In general, the compounds designed based on a sulfadiazine skeleton (compounds 4a1–6, 5a1–6) are more active than those obtained from sulfisoxazole (compounds 4b1–6, 5b1–6), and the N-(arylidene)hydrazinoacetyl sulfonamide derivatives 4a1–6, 4b1–6 are more active than their azetidionone analogues 5a1–6, 5b1–6.